New Findings of Species of the tribe Palpomyiini (Diptera: Ceratopogonidae) in Argentina - Spinelli, Gustavo Ricardo (2003)
New findings from Argentina, some of them notorious, of five species belonging to the tribe Palpomyiini are reported: Amerohelea pseudofasciata Grogan and Wirth and Bezzia venustula (Williston) from the Somuncura plateau, B. chilensis from Rio Negro, B. fluminensis from Corrientes, and Clastrieromyia uruguayensis from La Pampa.